Climate change adaptation in agriculture: practices and technologies. Opportunities for climate action in agricultural systems - Dinesh, Dhanush; Vermeulen, Sonja J. (2016)
In this info note we provide a brief overview of key agricultural practices and technologies which enhance productivity in a sustainable manner, thus contributing to food security and environmental goals while increasing the resilience of farming systems. A twinned info note considers higher-level measures of adaptation in agriculture, such as policies and institutions.